The Role of Gold Mining Companies in Increasing the Economy Through Empowering MSMEs in Batang Toru District - Septami Ayu Lestari Hasibuan; Waizul Qarni; Budi Dharma (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2024)
This study investigates the impact of gold mining on the local community and aims to enhance the economic well-being of the community, particularly through the empowerment of Micro, Small, and Medium Enterprises (MSMEs). Employing a qualitative research approach, the study focuses on MSMEs under the guidance of PTAR, selecting 10 informants from PTAR's partner MSMEs and 1 informant from the Small, Medium, and Enterprise (SME) Community Development Section via purposive sampling. Data collection methods include documentation and structured interviews, with subsequent data analysis, presentation, and conclusion formulation. The findings reveal that PTAR's empowerment program has successfully increased the capacity and economic independence of MSME actors and improved the quality of life for local communities through skills training, marketing access, and the provision of production equipment, marketing network assistance, and business permits. However, the study also identifies a need for enhanced monitoring and evaluation to ensure program effectiveness. These insights offer recommendations for developing more sustainable empowerment programs that foster harmonious relationships between companies and communities